Teaching methodology and perception of quality of life and stress in nursing students in northeastern Brazil (Research, Society and Development, 2021)
Objective: to evaluate the influence of the teaching-learning method on the perception of quality of life (QL) and stress among nursing students at a Brazilian federal university. Method: cross-sectional study carried out on two campuses of a public university, data collected through a questionnaire containing items for socioeconomic, academic and lifestyle habits, the WHOQOL-bref and the PSS-10, to assess QoL and perception of stress , respectively. Statistical analysis was performed using Fisher's Exact, Chi-square, T-test, ANOVA and Pearson's correlation tests. Results with p